Effects of drying techniques on composition of biomarker compounds (Sinensetin and rosmarinic acid) and antioxidant capacity of Misai Kucing leaves - ‘Adilah, Che Sulaiman (Universiti Malaysia Perlis, 2011)
Access is limited to UniMAP community.